A Study of Translingual Practices Expressed in a Social Application - Magdalena Kartikasari Tandy Rerung (Universitas Bunda Mulia, 2019)
Inspired from several articles that discussed about digital communication, the following article also discussed about the role of languages in some digital platforms such as Whatsapp. The study focused on a group of employees from various nationalities that work for the same company. The dominant language used is English yet most of the members were Indonesian. There are five examples provided from the group chatting that discuss various topics which are mostly related to the company matters. The methodology used was qualitative by observing the group chat activities and collecting the data from the screenshots. The pattern of translanguaging occurred in some parts of the conversation chatting, and the pattern was found based on the category of topic and relationship among the employees. On the other hand, the translingual practices expressed are the switching code from L1 to L2 when it depends on the situations and responses from the users.Keywords: translanguaging, digital communication, digital literacy